A workflow for learning objects lifecycle and reuse: Towards evaluating cost effective reuse - Sampson, Demetrios; Zervas, P. (2011)
Over the last decade Learning Objects (LOs) have gained a lot of attention as a common format for developing and sharing digital educational content in the field of technology-enhanced learning. The main advantage of LOs is considered to be their potential for component-based reuse in different learning settings supporting different learning activities. However, despite the importance of the concept of reuse and its potential benefits in digital educational content production and deployment, there are only sporadic efforts to study issues related to LOs reuse that would allow interested parties (such as people, organizations and initiatives) to assess the conditions for and eventually implement systematic LOs reuse within the context of learning activities design and development. This is a drawback in adopting the LOs paradigm towards reducing costs and effort. In this paper, we study existing efforts for the definition of the different steps involved during the LOs lifecycle, we identify the aspects of LOs reuse within the context of learning activities design and development, we propose a thorough workflow for LOs lifecycle that can support LOs reuse and enable us to define a set of metrics for cost effective LOs reuse, and discuss the cost effectiveness conditions in various use cases.